Evaluation of pharmacokinetics and safety of talazoparib in patients with advanced cancer and varying degrees of hepatic impairment. Issue 7 (18th March 2022) - Guo, Cen; Yu, Yanke; Chakrabarti, Jayeta; Piha‐Paul, Sarina A.; Moroose, Rebecca; Plotka, Anna; Shi, Haihong; Durairaj, Chandrasekar; Wang, Diane D.; Wainberg, Zev A.
Abstract : Aim: This phase I study investigated talazoparib pharmacokinetics (PK) and safety in patients with advanced solid tumours and varying degrees of hepatic function. Methods: Patients with advanced solid tumours and normal hepatic function or varying degrees of hepatic impairment (mild, moderate or severe, based on National Cancer Institute Organ Dysfunction Working Group classification) received talazoparib 0.5 mg once daily for 22 calendar days. Plasma and urine samples after single and multiple doses were collected and analysed for talazoparib using validated assays. Plasma PK data from all patients were analysed using the population PK method. Plasma and urine PK parameters in PK‐evaluable patients were calculated using noncompartmental analysis (NCA). Safety was monitored in all enrolled patients. Results: Thirty‐eight patients were enrolled; 37 had ≥1 PK concentration, among which 17 were evaluable for NCA. Population PK analysis (n = 37) indicated no significant impact of hepatic function on apparent clearance (CL/F) of talazoparib. Baseline creatinine clearance was the only significant covariate on CL/F ( α = 0.05). NCA of data (n = 17) showed no clear trend for increase in exposure on day 22 with worsening hepatic function. Talazoparib protein binding was comparable in patients with varying hepatic function. Talazoparib was generally well tolerated, and the safety profile observed in this study was consistent with the known safety profile of the drug. Conclusions: Hepatic impairment (mild, moderate or severe) has no impact on the PK of talazoparib. No dose modification is recommended for patients with advanced solid tumours and various degrees of hepatic impairment, and this labelling language has been approved by the US Food and Drug Administration and the European Medicines Agency.